Hydrogen-Dependent Nitrogenase Activity and ATP Formation in Rhizobium japonicum Bacteroids - Emerich, David W. (1979)
Rhizobium japonicum 122 DES bacteroids from soybean nodules possess an active H(2)-oxidizing system that recycles all of the H(2) lost through nitrogenase-dependent H(2) evolution. The addition of 72 μM H(2) to suspensions of bacteroids increased O(2) uptake 300% and the rate of C(2)H(2) reduction 300 to 500%. The optimal partial pressure of O(2) was increased, and the partial pressure of O(2) range for C(2)H(2) reduction was extended by adding H(2). A supply of succinate to bacteroids resulted in effects similar to those obtained by adding H(2). Both H(2) and succinate provided respiratory protection for the N(2)-fixing system in bacteroids. The oxidation of H(2) by bacteroids increased the steady-state pool of ATP by 20 to 40%. In the presence of 50 mM iodoacetate, which caused much greater inhibition of endogenous respiration than of H(2) oxidation, the addition of H(2) increased the steady-state pool of ATP in bacteroids by 500%. Inhibitor evidence and an absolute requirement for O(2) indicated that the H(2)-stimulated ATP synthesis occurred through oxidative phosphorylation. In the presence of 50 mM iodoacetate, H(2)-dependent ATP synthesis occurred at a rate sufficient to support nitrogenase activity. The addition of H(2) to H(2) uptake-negative strains of R. japonicum had no effect on ATP formation or C(2)H(2) reduction. It is concluded that the H(2)-oxidizing system in H(2) uptake-positive bacteroids benefits the N(2)-fixing process by providing respiratory protection of the O(2)-labile nitrogenase proteins and generating ATP to support maximal rates of C(2)H(2) reduction by oxidation of the H(2) produced from the nitrogenase system.